2008
DOI: 10.1590/s0104-66322008000200001
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for growth and biosynthesis of medium-chain-length poly-(3-hydroxyalkanoates) in Pseudomonas putida

Abstract: A kinetic model is presented giving a mathematical description of batch culture of Pseudomonas putida PGA1 grown using saponified palm kernel oil as carbon source and ammonium as the limiting nutrient. The growth of the micro-organism is well-described using Tessier-type model which takes into account the inhibitory effect of ammonium at high concentrations. The ammonium consumption rate by the cells is related in proportion to the rate of growth. The intracellular production of medium-chain-length poly-(3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…A good R 2 (0.96) for ethanol production and a significant ANOVA test confirmed that the model provides the relevant prediction The same results were obtained in several researches using the same model (Annuar et al, 2008). In addition, Jiménez-Islas et al (2014) found the effects of pH and temperature on ethanol production from red beet juice by t wo strains: S. cerevisiae ITD00196 and S. cerevisiae A TCC 9763.…”
Section: Ethanol Productionsupporting
confidence: 67%
See 1 more Smart Citation
“…A good R 2 (0.96) for ethanol production and a significant ANOVA test confirmed that the model provides the relevant prediction The same results were obtained in several researches using the same model (Annuar et al, 2008). In addition, Jiménez-Islas et al (2014) found the effects of pH and temperature on ethanol production from red beet juice by t wo strains: S. cerevisiae ITD00196 and S. cerevisiae A TCC 9763.…”
Section: Ethanol Productionsupporting
confidence: 67%
“…The coefficient of deter mination R 2 w as estimated to assess the accuracy of the estimated parameters achieved by fitting the experimental values to the proposed mathematical models. If R 2 approximate to 1, this coefficient justifies an excellent consistency of these equations (Annuar et al, 2008). Furthermore, the ANOVA …”
Section: Model Of Param Eters Estim Ationmentioning
confidence: 71%
“…Several kinetics models to describe the cell growth during biosynthesis of PHA in different bacterial species have been proposed (Annuar et al , 2008; Agarry et al , 2009; Baei et al , 2011). The culture conditions, nutrient limitation and the type of feeding substrates were reported to influence the structure, quantity and quality of polymer produced.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al (2011), while studying the synthesis of poly-3-hydroxybutyrate- co -3-hydroxyvelarate by mutant Pseudomonas putida KTOY06ΔC reported that change in substrates or precursors in fermentation media resulted in a defined composition of copolymer. Annuar et al (2008) reported that ammonium limitation in a medium efficiently encouraged PHA production in P. putida PGA 1. Recently, Rai et al (2011) reported the induction of synthesis of polyhydroxy-octanoate homopolymer in Pseudomonas mendocina CH50 by feeding sodium octanoate using two-stage seed culture techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Cited from [11] which supported the above conclusion by stating that one of the phases for producing starter is by growing the microbes in the proper medium and incubation process until it reached the optimum growth rate.…”
Section: Resultsmentioning
confidence: 80%